DAMPAK BANTUAN LUAR NEGERI JEPANG MELALUI SECOND KENNEDY ROUND (2KR) TERHADAP TINGKAT KESEJAHTERAAN PETANI DI INDONESIA TAHUN 2010-2015 - Desi Kartika Handayati (2021)
This study discusses the impact of the Second Kennedy Round (2KR) foreign aid provided as grant assistance from Japan in an effort to improve the welfare of farmers in Indonesia. The agricultural sector is a sector that drives the economy for Indonesia, where Indonesia can be said to be an agricultura l country, therefore the agricultural sector is one of the important factors in improving the welfare of farmers in Indonesia. Most of the people of Indonesia make their living as farmers, however, Indonesia still has many problems in the agricultural sect or, including a lack of knowledge, echnology and the lack of prosperity for farmers in Indonesia. This of course will hamper the welfare level of farmers where Indonesia should be able to become self-sufficient in food. In its implementation, the Second Kennedy Round (2KR) foreign aid was chosen by the Government of Indonesia because this assistance has been channeling its assistance to Indonesia in the agricultural sector for a long time. The method used is a qualitative method with a descriptive analysis approach. This research is supported by the theory of foreign aid and farmer exchange rates to examine the title of this research. The final result of this paper will try to show that in an effort to improve the welfare of farmers. The government certainly needs contributions from various parties, in this case Japanese foreign assistance through the Second Kennedy Round (2KR), which contributes to improving the welfare of Indonesian farmers.